Junctional Adhesion Molecule-A Is Highly Expressed on Human Hematopoietic Repopulating Cells and Associates with the Key Hematopoietic Chemokine Receptor CXCR4. (15th March 2016) - Chang, Chao-Hui; Hale, Sarah J; Cox, Charlotte V.; Blair, Allison; Kronsteiner, Barbara; Grabowska, Rita; Zhang, Youyi; Cook, David; Khoo, Cheen P.; Schrader, Jack B.; Kabuga, Suranahi Buglass; Martin-Rendon, Enca; et al.
Abstract: Hematopoietic stem/progenitor cells (HSPCs) reside in specialized bone marrow microenvironmental niches, with vascular elements (endothelial/mesenchymal stromal cells) and CXCR4-CXCL12 interactions playing particularly important roles for HSPC entry, retention, and maintenance. The functional effects of CXCL12 are dependent on its local concentration and rely on complex HSPC-niche interactions. Two Junctional Adhesion Molecule family proteins, Junctional Adhesion Molecule-B (JAM)-B and JAM-C, are reported to mediate HSPC-stromal cell interactions, which in turn regulate CXCL12 production by mesenchymal stromal cells (MSCs). Here, we demonstrate that another JAM family member, JAM-A, is most highly expressed on human hematopoietic stem cells with in vivo repopulating activity ( p  < .01 for JAM-A high compared to JAM-A Int or Low cord blood CD34 + cells). JAM-A blockade, silencing, and overexpression show that JAM-A contributes significantly ( p  < .05) to the adhesion of human HSPCs to IL-1β activated human bone marrow sinusoidal endothelium. Further studies highlight a novel association of JAM-A with CXCR4, with these molecules moving to the leading edge of the cell upon presentation with CXCL12 ( p  < .05 compared to no CXCL12). Therefore, we hypothesize that JAM family members differentially regulate CXCR4 function and CXCL12 secretion in the bone marrow niche. Abstract : Junctional adhesion molecule JAM-A is highly expressed on human hematopoietic repopulating cells and associates with the key hematopoietic chemokine receptor CXCR4. JAM-A High CD34 + UCB cells contain in vivo repopulating cells as demonstrated in primary and secondary transplanted NSG recipients. 2. Adhesion of UCB CD34 + cells to the bone marrow endothelial cell line BMEC-60 is partially inhibited with anti-JAM-A blocking antibody or after JAM-A knock-down. 3. JAM-A coimmunoprecipitates with CXCR4 when both are cotransfected into HEK293T cells. JAM-A moves to the leading edge of the UCB CD34 + cell with CXCR4 when cells are exposed to CXCL12. 4. We hypothesize that, while JAM-B and JAM-C can modulate CXCL12 production by bone marrow mesenchymal progenitor/stromal cells (MSCs) and adhesion of hematopoietic stem/progenitor cells (HSPCs) to bone marrow MSCs, JAM-A has a different role and instead coassociates with and regulates the function of CXCR4 on HSPCs as well as the adhesion of HSPCs to bone marrow endothelial cells, thereby enhancing retention of HSPCs in specialized bone marrow vascular niches.